A screening study of the spatial distribution and cumulative toxicity of agricultural pesticides in the European Union’s waters - Pistocchi, A.; Dorati, C.; Galimberti, F.; Udias, A.; Bopp, S.; D’Andrimont, R.; Catarino, R.; Schaefer, R. B. (Frontiers in Environmental Science, 2023)
Pesticides can be an important stressor to aquatic ecosystems, and their use is strictly regulated in the European Union. However, data on the use of pesticides are rather limited and poorly available, and monitoring is often insufficient to characterize their actual exposure and impact. In this contribution, we present an assessment of concentrations and toxicities of 148 pesticide active substances (AS) for the whole European Union (EU), based on available estimates of their use in agriculture and a simple screening-level model of their fate and transport. We show that the model quantifies pesticide concentrations in the same orders of magnitude of the monitoring data available at European scale. Using the model as a first-approximation representation of pesticides distribution in the EU, we analyse the cumulative toxicity of pesticides in the soils and stream network of the EU. We estimate that individual substances are generally below no observed effect concentrations (NOEC) for aquatic organisms. However, the cumulative mixture toxicity (calculated by adding individual AS concentrations divided by the respective NOEC) can exceed 0.1 toxic units (TU) for more than 27% of the length of the EU’s stream network, and 1 TU for more than 4%. The cumulative toxicity at a given location is driven by only a handful of AS, but these differ from site to site reflecting the variability of pesticide use. Still, we estimate that only about 20 AS out of 148 appear among the top 10 contributors to cumulative toxicity in most cases. While our assessment suggests a relatively widespread risk due to pesticide pollution, it also points to the important limitations concerning knowledge of pesticide use and monitoring of pesticide occurrence in the environment. These limitations need to be addressed in order to evaluate more accurately the effectiveness of EU pesticide policies. The assessment represents a proof-of-concept of a method that can be applied in support of the monitoring of pesticide policies implementation in the EU.